Performance analysis and optimization of oleophobic coalescing filter element at high gas velocity - LI Yipu; CHEN Feng; SUN Yong; JIA Haojie; GAN Jie; YU Wenhan; JIAO Quan; JI Zhongli (You-qi chuyun, 2023)
In the long-distance transportation of natural gas, the oleophobic coalescing filter element will experience secondary entrainment and a decrease in filtration efficiency when the gas velocity is too high. Herein, an testing device for the filtration performance of the gasliquid coalescing filter element was established according to the relevant test standards. The effects of the precision grade of the filter element, the material of the drainage layer and the punching height of the inner skeleton on the filtration performance of the oleophobic coalescing filter element under high gas velocity were studied and analyzed. The results show that the high-precision filter material is easy to cause the accumulation of liquid between the last layer of filter material and the drainage layer during filtration at high gas velocity, resulting in the high-precision filter material failing to achieve the optimal filtration effect. Instead, the filter material with moderate precision has the best filtration performance. When the material of the drainage layer is changed to primary felt and sponge,the pressure drop in the channels of the filter element is reduced, the drainage speed of the last filter material layer is accelerated, the liquid accumulation between the last filter material layer and the drainage layer is mitigated, and the secondary entrainment of the filter element is significantly weakened. The secondary entrainment of the filter element can be effectively reduced when the punching height in the inner skeleton is 2 cm from the bottom of the filter element.